City of bones - Clare, Cassandra (New York : Simon Pulse, 2008)
Suddenly able to see demons and the Darkhunters who are dedicated to returning them to their own dimension, fifteen-year-old Clary Fray is drawn into this bizarre world when her mother disappears and Clary herself is almost killed by a monster.
Keywords: Demonology -- Juvenile fiction; Fantasy fiction